The Gothic and theory : an Edinburgh companion - Hogle, Jerrold E.; Miles, Robert, 1953- (Edinburgh companions to the gothic., 2019)
This collection provides a thorough representation of the early and ongoing conversation between Gothic and theory - philosophical, aesthetic, psychological and cultural.